2020
DOI: 10.1016/j.jenvman.2019.109653
|View full text |Cite
|
Sign up to set email alerts
|

Coping with waste: A government-NGO collaborative governance approach in Shanghai

Abstract: Complex environmental issues are leading local governments to collaborate with non-governmental organizations (NGOs) in the urban environmental governance sphere. While previous studies have emphasized how the Chinese government engages NGOs in service contracting to meet rising service demands, they have not provided empirical evidence of the outcomes of these collaborations at a local level. Based on a mixed methods research design developed from May 2016 to February 2017 in Shanghai, the impact of Aifen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…For instance, an integrated approach targets institutions such as governments, industry, educational organizations, and the local villages (Halkos and Petrou 2020). This can be undertaken through the establishment of educational centres on a municipal level, through the activities of NGOs, and in schools and universities (Arantes et al 2020). Local media such as radio stations and posters can be an effective medium to ensure information is proliferated through the community.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…For instance, an integrated approach targets institutions such as governments, industry, educational organizations, and the local villages (Halkos and Petrou 2020). This can be undertaken through the establishment of educational centres on a municipal level, through the activities of NGOs, and in schools and universities (Arantes et al 2020). Local media such as radio stations and posters can be an effective medium to ensure information is proliferated through the community.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Presently, the literature review shows that environmental NGOs are widely studied in its influence on environmental mitigation strategies such as environmental management (Arantes, Zou, & Che, 2020;Shaharudin & Fernando, 2015), firms' collaboration (Mousavi & Bossink, 2020;Krabbenborg, 2020), a relationship with diseases (Saadat, Rawtani, & Hussain, 2020) and governance (Khan et al, 2020;Hale, 2020). Based on the current studies available in the literature, it is evident that there exists an extensive literature on environmental NGOs for a considerable period in many fields of studies.…”
Section: Malaysia Environmental Ngosmentioning
confidence: 99%
“…Study by Rabbani et al (2020) confirmed to be true the 'assumption that by allocating budget (funds) to NGOs for increasing consumer environmental awareness (CEA), the produced waste will be decreased. Similarly, a study in Shanghai by Arantes et al (2020) revealed that NGOs are very effective intermediaries between state and society in promoting environmental governance practices, and that a collaborative governance model can enhance public participation in waste classification, among other things, in urban areas. Tukahirwa (2011) reported national and international NGOs involved in SWM activities in in East African countries of Uganda and Kenya such as advocacy services, capacity building, community sensitisation and mobilisation, recycling, construction of latrines, garbage collection, monitoring and advisory services, supporting other NGOs amongst others.…”
Section: Introductionmentioning
confidence: 99%